Important issues of providing genetic services in Serbia from the perspective of medical law - Mujović-Zornić, Hajrija M. (Medicine, law & society, 2016)
Medico-legal issues that arise from the work of genetic health services became in recent time very current, especially regarding the Serbian law issues and dilema how to treat rare deseases patients among other voulnerable groups, whish often were not recognized in society. The legal system shall be an important mechanism, which could help by giving some solutions concerning the relations, rights and obligations of all parties in providing genetic services (informing, counseling, testing, keeping privacy). The law is invited to establish a delicate balance between legal qualification and more practical issues. In many countries there are medical guidelines for health professionals and biologists who work in the area of human genetics, according to which is done the essential rules for medical proceedings, with also significant parameters for legal decisions. Sometimes the legal situation is more complex when it includes malpractice cases due to violation of rights or breach of professional duties and contractual obligations in genetics. All issues should be consider from the aspect of Serbian legislator efforts to make a new codification in the area of genetic dignostics, which is adopted in January 2015.
Keywords: case of Serbia; human rights; legislation; medical genetic